Effect of Teaching Geometry by Slow-Motion Videos on the 8th Graders’ Achievement - al khateeb, Mohammad Ahmad; Alduwairi, Ahmed Mohammad (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This study aims to investigate the effect of slow-motion videos use on the 8th graders’ achievement in geometry, and identify the students’ views about the slow-motion. The study was carried out in a quasi experimental environment on 74 eighth graders of two different classes. One of the classes was designated as the experimental group (n=38). The other class (n=36) were designated as the control group,. The results showed that the achievement level of the students who attended the geometry lessons using the slow-motion mode was higher than those who attended the traditional method lessons. Furthermore, the results showed that the experimental group students found that learning through slow-motion was: information, Easy understandable, Beneficial, instructive, Stimulating, enjoyable, Very creative .